Environmental drivers of the composition and distribution of larval fish assemblages off the south coast of South Africa - Trassierra, Jaqueline Anne (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2019)
The species composition, distribution and patterns of vertical migration of larval fish assemblages were investigated in March and in September 2013 within two adjacent log spiral bays, Algoa Bay and St Francis Bay, on the south coast of South Africa. Fish larvae were collected by means of a boat towed bongo net (57 cm diameter; mesh aperture 500 Î¼m). An onshore (2 km) and an offshore (3 km) station were each sampled twice during the daytime (06:00 "“ 18:00) with two horizontal tows: near the surface (0.5 m) and close to the bottom (12 m). Tows were repeated at night (18:00 "“ 23:00) for onshore sites. Larval catches included 16 fish families and 40 species. A multivariate analysis indicated that the species composition was significantly different between Algoa Bay and St Francis Bay, with Engraulidae, Blenniidae, Sparidae, Soleidae and Cynoglossidae making important contributions to the larval fish catch in Algoa Bay, while Blenniidae, Engraulidae, Tripterygiidae, Sparidae and Gobiesocidae contributed significantly in St Francis Bay. Differences in assemblage composition were noted between the Spring (September"“October) and Autumn (March-April) months. The species composition of larval fish assemblages was related to wind speed, wave height, cloud cover, sea water temperature, depth, average current speed and direction. Wind speed, wave height, temperature and depth significantly contributed to the variation in larval fish densities. Abundances of larval fishes were greater offshore than onshore, larvae from pelagic eggs dominated catches offshore, while larvae from demersal eggs dominated onshore catches. Habitat structure strongly influenced the composition of larval fishes between the bays and abundances were significantly greater at night than during the day. Most larval fishes displayed a reverse diel vertical migration pattern and were most influenced by predators, wind speed and cloud cover. This study shows that larval fish assemblages are highly complex and patchy. Spawning mode, individual species behaviour, diel vertical migration, current structure, depth, temperature, wind speed, cloud cover and type of habitat substratum all influence larval fish composition and distribution in the nearshore waters of South Africa.
Keywords: Fishes -- Larvae -- South Africa -- Eastern Cape; Fishes -- Larvae -- Migration -- South Africa -- Eastern Cape; Fishes -- Larvae -- Dispersal -- South Africa -- Eastern Cape